ISH NIA PS 01-06 Downregulation of endothelial TRPV4 channel contributes to the reduced endothelium-dependent hyperpolarization in genetically hypertensive rats. (September 2016) - Seki, Takunori; Goto, Kenichi; Kiyohara, Kanako; Kansui, Yasuo; Murakami, Noboru; Haga, Yoshie; Ohtsubo, Toshio; Matsumura, Kiyoshi; Kitazono, Takanari
Abstract : Objective: Endothelium-dependent hyperpolarization (EDH)-mediated responses are decreased in hypertension. However, the underlying mechanisms have not yet been determined. Several recent studies have suggested that Ca 2+ influx through endothelial transient receptor potential vanilloid 4 channel (TRPV4) plays a role in EDH-mediated hyperpolarization via the downstream activation of small- and intermediate-conductance of Ca 2+ -activated K + channels (SKCa and IKCa). The present study was designed to elucidate whether the impairment of EDH-mediated responses in hypertension is attributable to the dysfunction of TRPV4 and/or KCa. Design and Method: Conventional electrophysiological and molecular biology techniques were used in isolated superior mesenteric arteries of 20-week-old stroke-prone spontaneously hypertensive rats (SHRSP) and age-matched Wistar-Kyoto (WKY) rats. Results: In the WKY mesenteric arteries, acetylcholine (ACh)-induced, EDH-mediated relaxations were reduced by a combination of KCa blockers (apamin plus TRAM-34), and by the blockade of TRPV4 with the selective antagonist RN-1734 or HC-067047. In the SHRSP mesenteric arteries, the ACh-induced, EDH-mediated hyperpolarization and relaxation were significantly smaller compared with those of WKY. GSK1016790A, a selective TRPV4 activator, evoked robust hyperpolarization and relaxation in WKY arteries. In contrast, in SHRSP arteries, the GSK1016790A-evoked hyperpolarization was small and relaxation was absent. Hyperpolarization and relaxation in response to CyPPA, a selective SKCa activator, were marginally decreased in SHRSP arteries compared with those of WKY. On the other hand, hyperpolarization and relaxation in response to 1-EBIO, a selective IKCa activator, and to levcromakalim, an ATP-sensitive K + channel opener, were comparable between groups. The expression of endothelial TRPV4 and SKCa protein were significantly decreased in the SHRSP mesenteric arteries compared to those of WKY. Conclusions: These findings suggest that downregulation of endothelial TRPV4 predominantly underpins the reduced ACh-induced, EDH-mediated responses in mesenteric arteries of SHRSP.